A Power Quality Improvement for Microgrid Inverter Operated In Grid Connected and Grid Disconnected Modes - M. Tamil Selvi; D.G unapriya (Institute of Advanced Engineering and Science, 2014)
The renewable energy based distributed generators (DGs) will plays a dominant role in electricity production. A micro grid consists of clusters of load and distributed generators that operate as a single controllable system. The interconnection of the DG to the utility/grid through power electronic converters has raised concern about safe operation and protection of the equipments. The main objective of this paper is too focused on the power quality improvement in micro grid. In the distributed power system, the increased infiltration of nonlinear loads and power electronic interfaced distribution generation systems creates power quality issues such as voltage unbalance, frequency regulation and harmonic elimination.